EVALUASI PERTUMBUHAN PANJANG SPESIFIK IKAN PATIN (Pangasius sp.) MELALUI PENAMBAHAN EKSTRAK DAUN KELOR DAN VITAMIN E PADA PAKAN - Radhi Fadhillah; Zulfadhli Zulfadhli; Muhammad Arif Nasution; Burhanis Burhanis (Universitas Teuku Umar, 2022)
Siamese catfish (Pangasius sp.) is one of the fresh water commodity that has great prospects because it has a fairly high selling value as well as the culture methods that are not difficult to developmentas. The research was conducted for 60 days..This study aims to evaluate the addition of moringa leaf extract and vitamin E to increase long growth and also increase the efficiency of utilization of siamese catfish seed feed. The method used is the experimental method, namely Completely Randomized Design (CRD) with 4 levels of treatment and 4 replications, the details of the treatment are as follows: A). Controls: Commercial Feed; B). Commercial Feed + EDK 100mL/kg feed + Vit. E 200 mg/kg feed; C). Commercial Feed + EDK 150 ml/kg feed + Vit. E 200 mg/kg feed; D). Commercial Feed + EDK 200 ml/kg feed + Vit. E 200 mg/kg feed. The results showed that the addition of Moringa leaf extract as much as 150 ml/kg feed and vitamin E as much as 200 mg/kg feed was the best treatment and showed a significant effect (P<0.05) on specific growth in length (1.07 ± 0.22% / day), feed use efficiency (84.21 ± 7.26%) and total feed consumption (200.00 ± 0.82g).